Complete Genome Sequence of Staphylococcus aureus Z172, a Vancomycin-Intermediate and Daptomycin-Nonsusceptible Methicillin-Resistant Strain Isolated in Taiwan - Chen, Feng-Jui (American Society for Microbiology, 2013)
We report the complete genome sequence of Z172, a representative strain of sequence type 239-staphylococcal cassette chromosome mec type III (ST239-SCCmec type III) hospital-associated methicillin-resistant Staphylococcus aureus in Taiwan. Strain Z172 also exhibits a vancomycin-intermediate and daptomycin-nonsusceptible phenotype.